2020
DOI: 10.3390/en13071715
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Flat Plate and Vacuum Tube Solar Collectors by Applying a MWCNT/Fe3O4 Binary Nanofluid

Abstract: This study experimentally investigated the performance characteristics of water and MWCNT/Fe3O4 binary nanofluid as a working fluid in a flat plate and vacuum tube solar collectors. As a result, the highest efficiency was 80.3% when 0.005 vol.% MWCNT/0.01 vol.% Fe3O4 binary nanofluid was applied to the flat plate solar collector, which was a 17.6% increase in efficiency, compared to that when water was used. In the case of the vacuum tube solar collector, the highest efficiency was 79.8%, which was 24.9% highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 35 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Under varying mass fluxes (420 kg/s m 2 and 598 kg/s m 2 ) and mixing volume concentrations, the efficiency of MWCNT (0.003 vol% and 0.005 vol%) + Fe 3 O 4 (0.01 vol% and 0.015 vol%) NFs as working fluids was investigated in an FPSC [ 117 ]. They noticed that the collector efficiency was improved as the mass flux and MWCNT concentration increased and Fe 3 O 4 concentration decreased.…”
Section: Solar Energy Application Of Hybrid Nanofluidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under varying mass fluxes (420 kg/s m 2 and 598 kg/s m 2 ) and mixing volume concentrations, the efficiency of MWCNT (0.003 vol% and 0.005 vol%) + Fe 3 O 4 (0.01 vol% and 0.015 vol%) NFs as working fluids was investigated in an FPSC [ 117 ]. They noticed that the collector efficiency was improved as the mass flux and MWCNT concentration increased and Fe 3 O 4 concentration decreased.…”
Section: Solar Energy Application Of Hybrid Nanofluidsmentioning
confidence: 99%
“…Lee et al [ 117 ] experimented the deployment of MWCNT (0.003 vol% and 0.005 vol%) + Fe 3 O 4 (0.01 vol% and 0.015 vol%) NFs as working fluids in a vacuum tube solar collector under varying mass fluxes (420 kg/s m 2 and 598 kg/s m 2 ) and mixing volume concentrations. The results demonstrated that the highest efficiency was achieved using MWCNT (0.005 vol%) + Fe 3 O 4 (0.01 vol%) NF and at a mass flux of 598 598 kg/s m 2 .…”
Section: Solar Energy Application Of Hybrid Nanofluidsmentioning
confidence: 99%
“…Also, the maximum electrical and thermal efficiencies of the solar collector were 15% and 82% of the hybrid nanofluids at the peak of solar radiation, respectively Alawi et al (Alawi et al 2019 ) Experimental Pentaethylene glycol Treated graphene nanoplatelets 0.025 0.05 0.075 0.1 According to the outcomes, the collector efficiency used with the nanofluid went up by a maximum of 13.3% compared to water Rajput et al (Rajput et al 2019 ) Experimental Water Al 2 O 3 0.1 0.2 0.3 The outcomes displayed that with increasing the volume fraction, a 21.32% go up in collector efficiency was observed Hussein et al (Hussein et al 2020 ) Experimental Distilled water Hexagonal boron nitride (h-BN)-graphene nanoplatelets (CF-GNPs) with covalent functionalized-multi wall carbon nanotubes (CF-MWCNTs) 0.05 0.08 0.1 Solar collector efficiency has been got up by up to 85% with hybrid nanofluids. In addition, raising the concentration of nanoparticles increases the thermal energy and temperature of the fluid outlet Moravej et al (Moravej et al 2020 ) Experimental Water TiO 2 1 3 5 According to the results shown, with increasing solar radiation, the impact of adding nanoparticles increased so that the maximum collector efficiency when using nanofluid was reported to be approximately 78% Aghili and Kasaeian (Aghili Yegane and Kasaeian 2020 ) Numerical Water Hybrid nano (Al 2 O 3 /CuO) 0.05 0.1 The thermal efficiency went up using a combined nanofluid Lee et al (Lee et al 2020 ) Experimental Water MWCNT/Fe 3 O 4 0.003 0.0...…”
Section: Flat Plate Solar Collectors With Nanofluidsmentioning
confidence: 99%
“…Due to the escalating concern over the global climate and the pervasive issue of PM2.5 (particulate matter with a diameter of 2.5 μm or less) across the world, the majority of developed countries are actively considering the adoption of renewable energy policies 1,2 . Therefore, along with establishing and implementing energy policies that increase the use of green energy globally, activities related to these energies are also growing 3,4 …”
Section: Introductionmentioning
confidence: 99%